The political economy of health in Brazilian territory and its industrial complex: an analysis based on the concept of productive space circuit - Antas Jr, Ricardo Mendes (Sociedade & Natureza, 2017)
The political economy of health in Brazilian territory is based mainly on the constitutional guarantee thathealth is a citizen’s right and a State’s duty. However, this right came into force only after the FederalConstitution in 1988. At the time of its proclamation, the country’s population was 145 million people,and the new constitutional law increased even more demands for industrial products aimed at Medicalattention. Health as a right property has led to the transition from a national industrial sector to the esstablishment of the current transnationalized industrial health complex, which monopolizes much of thesupply of the necessary inputs to the national health system organized and regulated by the Unified HealthSystem. This process witnessed the entry of transnational companies in the health sector and the intensegrowth of finished goods flows and semi manufactured industrial inputs, evidencing the consolidationof new characteristics in the territorial division of labor. We analyze the industrial health complex inBrazilian territory based on the concept of productive space circuit, as proposed by Santos (1988).